PERBAIKAN SIFAT MEKANIK DODOS KELAPA SAWIT PRODUK LOKAL MELALUI PROSES PACK CARBURIZING DAN MODIFIED MARTEMPERING - Yunaidi Yunaidi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
This paper aims to enhance the quality and service life of local product oil palm harvesting chisels so that they can compete with imported products, which until now are mostly used by oil palm harvesters in Indonesia. To achieve these objectives, the method of improving the mechanical properties of chisels was chosen through the pack carburizing and modified martempering processes. Chisels of local products can be improved in quality, especially their hardness and impact strength through the modified martempering or pack carburizing heat treatment process followed by modified martempering. Heat treatment of modified martempering at an oil cooling temperature of 1250 C followed by tempering at a temperature of 4500 C can increase the impact strength of chisels up to 12% higher than chisels without heat treatment, while its hardness can increase up to 29%. Heat treatment of pack carburizing followed by modified martempering at an oil cooling temperature of 1750 C and tempering at a temperature of 4500 C can increase the impact strength up to 65% and the hardness increases up to 27%.